First case report of an acute hepatitis E subgenotype 3c infection during pregnancy in Germany - Tabatabai, Julia; Wenzel, J. J.; Soboletzki, Monica; Flux, C.; Navid, Mojdeh Heidary; Schnitzler, Paul (Clinical and diagnostic virology, 2014)
Hepatitis E is usually a self-limiting disease and an important cause of acute hepatitis in endemic countries in Asia and Africa. However, the mortality rate for pregnant women infected with hepatitis E virus (HEV) in this area is about 25%. In Germany, sporadic cases of acute hepatitis E infections have been described and the number of autochthonous infections is increasing. Here we report an autochthonous HEV subgenotype 3c infection in a 27-year old pregnant woman. This is the first documented case of a hepatitis E infection during pregnancy in Germany. The patient presented in week 26 of gestation with acute hepatitis and elevated transaminases. During follow-up, she tested positive for anti-HEV antibodies. HEV viral load during the acute hepatitis was 2.3×106 copies/ml serum, however viremia declined and cleared rapidly. Sequence analysis revealed a HEV subgenotype 3c closely related to European isolates. The patient had not travelled outside Germany, had regular contact to animals, but the source of infection remains unclear. The newborn was delivered in week 40 of gestation in good health, HEV was not transmitted and liver enzymes were normal. In conclusion, hepatitis E should be considered in differential diagnosis in patients with acute hepatitis especially during pregnancy, even without travel history to countries with high endemicity.
Gesehen am 16.09.2020